The Hirsch Institute of Tropical Medicine Asella, Äthiopien - Häussinger, Dieter (De Gruyter, 2019)
In 2013, the Hirsch Institute of Tropical Medicine was officially inaugurated as a branch of the Department of Gastroenterology, Hepatology, and Infectious Diseases at Heinrich Heine University Düsseldorf under the direction of Professor Dieter Häussinger. The HITM serves as a place of scientific medical knowledge transfer, postgraduate medical training, and of conducting scientific projects relating to tropical medicine and infectious diseases.